Effects of clothes on hyperpigmentation and sunburn on people of India - Kundu, Ananya; Kundu, Aditya (International Journal of Research in Dermatology, 2024)
Background: Many people suffer from sunburn and hyperpigmentation. Solar radiation can lead to hyperpigmentation as it easily triggers the production of melanin. Hyperpigmentation, sunburn and skin aging is determined by genetic aspects, lifestyle, and environmental factors. So, clothes likely to influence solar radiation related sufferings. The objective of the study is to test if suffering from solar radiation is associated with the nature of clothes used by the persons, what extent clothes can provide protection against solar radiation, and which type of clothes can provide maximum protection. Methods: The Cohort study methods used for this study. The study done in two stages, first stage pilot study conducted to validate the instruments and methods used in the study. Second stage is the data collection and analysis for statistical testing and hypothesis testing. Results: Persons wearing dark coloured loose and thick clothes covering most of their body parts can get 15 times more protection compared to the persons wearing light coloured tight and thin clothes covering less body parts. Conclusions: People can protect themselves from solar radiation in an affordable manner by choosing appropriate clothing.